Formation and Development of School Education of the Autonomies of the Middle Volga Region, 1920-1930s - Elena K. Mineeva; Alevtina P. Zykina; Alexey I. Mineev (RUDN Journal of Russian History, 2022)
The study is devoted to the analysis of the process of formation of the Soviet system of school education in the 1920-1930s. The policy of the Soviet government in this area and its specific results are also considered. The authors find out that the experiments, carried out in the course of reforming education, were accompanied by both positive and negative paradigms. Of the positive results that were already observed by the end of the 1920s, the quantitative changes, marked by an increase in the number of educational institutions, as well as the number of teachers and students, stand out in particular. Of the positive results that were already observed by the end of the 1920s, there particularly stand out the quantitative changes marked by an increase in the number of educational institutions, as well as the number of teachers and students. Also progressive, although slower, was the strengthening of the material and technical base of schools. Large-scale transformations related to the destruction of the old Russian school and the construction of a new Soviet school took place against the backdrop of important historical events (the Civil War, famine, industrialization and collectivization, etc.), which influenced the course of the modernization processes. Along with objective factors, the development of the educational sphere was also affected by subjective reasons: the dissatisfaction of the population with certain measures in the field of schooling, the conservative views of the peasant population, etc. As a result, in the early 1930s, the course of the Soviet government with regard to the general education school was revised. In order to correct the mistakes made, the Soviet government had to return to the traditional class-and-lesson system. In the 1930s, there increased the budgetary financing of the school education system. The policy pursued allowed the Soviet state to achieve noticeable results in improving literacy of the population, quantitative expansion of primary and secondary education, qualitative improvement of the level of education in general.